Assessing Operational Performance Under Cyberattacks - Ahmed, Dania; Martínez, Felipe; Vinš, Marek; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The NotPetya cyberattack's impact on Maersk has been examined from several technological, security, and IT perspectives, but lacks an operational management perspective. This Bachelor's Thesis assessed the company’s performance based on five operational goals of quality, speed, dependability, flexibility, and cost. A Likert scale assessment has been prepared to evaluate the company’s performance before and after the attack and to provide a statistical analysis using a paired t-test. Overall, significant drops in performance were observed across all five operational goals due to the cyberattack on digital systems, with speed and cost experiencing the largest losses. In addition, average comparisons revealed further declines in operational reliability and responsiveness due to the cyberattack’s impact on digital systems. The thesis proposes strategies to enhance cyber resilience in global logistics operations.
Vedoucí práce: Felipe Martínez
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses